Ebû Hanîfe’ye Yöneltilen Eleştiriler - Aci̇mamatov, Zaylabidin (Dinî araştırmalar, 2006)
Criticisms to Abû Hanife. Abû Hanife was described as belonging to the Ashâb al-Ra'y, since he paid much attention to the reasoning as well as the Qur'an and Hadith. Those who criticized and accused him of being ignorant in hadith were the Ashâb al-Hadith. Abu Hanife lived in a period that the fabrication of hadiths was extremely widespread. For this reason, he used in his works a small number of hadiths. In the time of Abu Hanife the hadiths were not yet compiled completely. Since Abû Hanife supported the Murjite views of Hadith, he was described by the Ashab al-Ray as a Murjite. In order to understand the connection between Murjia and Abû Hanife is to make comparison between the Murjite views and Abû Hanifa's views of faith